Post-traumatic Stress Disorder And Psychological And Social Adjustment Among Libyan Who Participated In 17th Of February Revolution: A Structural Equation Modeling Analysis - Fariha Omar M. Elfaydi; Ibrahim Mikail; R. A. H. Kirembwe (International Association of Computer Science and Information Technology (IACSIT) Press, 2024)
Non-Indexed Publication